ITSBAT ON WIDOW'S MARRIAGE DURING IDDAH: OVERVIEW ON THEORY OF NORM HIERARCHY (Study of Stipulation Number 137/Pdt.P/2018/PA.Bm) - Tobroni, Faiq (Jurnal Hukum dan Peradilan, 2022)
The presence of legal norm hierarchy theory can be used to describe legal events that cannot be resolved only by concrete legal norms. This paper will elaborate on this theory and its implementation to explain the legal considerations behind the acceptance of istbat of widow marriages during the iddah period as occurred in Stipulation Number 137/Pdt.P/2018/PA.Bm. By using qualitative methods and secondary data, this article concludes that the legal consideration of judges for accepting this case is the nescience, child protection, and absence of bad willing. The construction of legal considerations in this case represents the movement of selecting norms from al-ahkam al-far`iyyah to al-usul al-kulli and al-qiyam al-asasi.